Diagnostics of specific working capability and evaluation of adaptation to training workload during sport season in open water swimmers - Petriaev, A. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Regular evaluation of functional diagnostics tests is needed in order to increase the efficiency of active control in the process of monitoring of functional state of the swimmer, and the tests must be conducted in circumstances specific for the precise type of sport. At the same time the specifics of muscular activity and the orientation of the training process are defining the features of the diagnostics of functional state of the swimmers, which is, in turn, oriented to control the adaptation processes of those systems and functions of the swimmer's body that are principal for swimming in open water. The bio-energetic potential is a key factor for achieving high results for swimmers who compete on long and very long distances. E. Maglischo's 'Swimming fastest' is going through the issue of evaluation the aerobic and anaerobic capacities of swimmers in detail. Around 10 methods are given to individually estimate the aerobic and anaerobic threshold using the invasive procedure of measuring the blood lactate and it is pointed out that each of them we can use for the gathered data correlates well with aerobic efficiency of swimmers [1]. Nevertheless, the static values of lactate are also used in training practice as they allow to trace the dynamics of the bio-energetic potential of the swimmer via standard protocol which allows us to evaluate the quality of work objectively over the year. The aim of this study was to design a method for diagnostics of specific working capability of swimmers in open water with a specific competitive activities